Fire in the hole! - Farrell, Mary Cronk (Clarion Books, 2004)
A claustrophobic boy dreams of going to college and becoming a newspaperman rather than a miner like his father, but when all union miners in the Coeur d'Alene Mining District are arrested, Mick develops new respect for his father while taking over responsibility for his family.